(untitled) (International Journal of Engineering and Computer Science, 2016)
The wireless mesh network is a new emerging technology that will change the world of industrial networks connectivity to more efficient and profitable. Mesh networks consist of static wireless nodes and mobile customer; have emerged as a key technology for new generation networks. The Quality of Service (QOS) is designed to promote and support multimedia applications (audio and video), real time. However guarantee of QoS on wireless networks is a difficult problem by comparison at its deployment in a wired IP network. This paper focuses to enhance an efficient Cluster Based Routing protocol Q-CBRP for random mobility model for mesh clients using varying traffic such as HTTP , FTP and video streaming and measure the different criteria of QoS in a mobile WMN